2017
DOI: 10.18203/2349-2902.isj20175907
|View full text |Cite
|
Sign up to set email alerts
|

Surgery without knife: an ideal treatment for lactational breast abscess

Abstract: INTRODUCTIONBreast abscess is common in lactating females. The incidence of breast abscess ranges from 0.4 to 11% of all lactating mothers.1 Risk factors for the development of breast abscess are milk stasis by duct blockage, stress, sore nipples or infrequent breastfeeding. Other risk factors for abscess formation include maternal age over 30 years, gestational age greater than 41 weeks and a history of mastitis. The pathogen most commonly Staphylococcus aureus enter into breast via cracked nipple specially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Ultrasound guidance was used in the NA group in six trials [ 19–23 , 25 ]. Four included trials [ 1 , 19 , 20 , 23 ] mentioned the analysis of pathogens causing breast abscesses and found that the predominant pathogen was Staphylococcus aureus . In eight trials [ 1 , 19–23 , 25 , 26 ] patients were simultaneously treated with antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound guidance was used in the NA group in six trials [ 19–23 , 25 ]. Four included trials [ 1 , 19 , 20 , 23 ] mentioned the analysis of pathogens causing breast abscesses and found that the predominant pathogen was Staphylococcus aureus . In eight trials [ 1 , 19–23 , 25 , 26 ] patients were simultaneously treated with antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Breast fistula was the most frequently reported complication of breast abscess, especially in puerperal patients, and the incidence of breast fistula was extracted from five included trials [ 19 , 22 , 23 , 25 , 26 ]. All patients included in these studies were puerperal abscesses and heterogeneity between the included trials was low ( I 2 = 0%, p = .994).…”
Section: Resultsmentioning
confidence: 99%